Slow- Release Fertilizer Formulation Using Acrylic and Chitosan Coating - Handayani, Lili; Djajakirana, Gunawan; Darmawan, .; Munoz, Canecio Peralta (UNIVERSITY OF LAMPUNG, 2015)
The low-efficiency problem in fertilizer application can be overcome by controlling fertilizer solubility, i.e. by rendering the fertilizer to be released gradually; such material is also known as slow-release fertilizer (SRF). This research was aimed to formulate SRF by coating technique using acrylic and chitosan as the coating material, and to evaluate fertilizer resistance to too fast disintegration, and rate of nutrient release method. The results demonstrated that fertilizer formulation containing N, P, K, Fe, Cu, and Zn with granulation technique yielded 74% of granules with 2-5 mm in diameter. The SRFs (formulated fertilizer with acrylic or chitosan coating) were more resistant to water pounding than non-SRF. Furthermore, shaking test with distilled water or 2% citric acid, or by percolation test with distilled water showed that the SRFs had lower nutrient solubility than the non-SRFs. The results of shaking test also specifically indicated that coating with acrylic made the fertilizer more resistant to the citric acid,suggesting that this coating material would be more suitable in acidic soils. The SRFs formulated with the addition of chitosan during blending of micronutrients prior to mixing with macronutrients, granulation, and final coating exhibited lower nutrient solubility than the SRFs without the pre-coating chitosan addition. [How to Cite: Lili H, G Djajakirana, Darmawan, and CP Munoz. 2015. Slow- Release Fertilizer Formulation Using Acrylic and Chitosan Coating. J Trop Soils 19: 37-45. Doi: 10.5400/jts.2015.20.1.37][Permalink/DOI: www.dx.doi.org/10.5400/jts.2015.20.1.37]